Elaboração e análise de indicadores de educação ambiental para a conservação da biodiversidade mediada pela tecnologia no Parque Nacional do Iguaçu - Santos, Milena Ricco dos (Universidade Federal de São Carlos, 2022)
This research considered the still unexplored potential when articulating the principles and guidelines of environmental education for the conservation of biodiversity to the use of technology in conservation units. Thus, with the lack of practical instruments for environmental educators to evaluate educational processes in non-formal education spaces, the main objective of this research was to elaborate, test and analyze the use of environmental education indicators for the context of an environmental education mediated by the use of a mobile application in a conservation unit with a large flow of visitors - the Iguaçu National Park (PNI). The research stages involve the elaboration of initial indicators based on bibliographic research; the validation process with professionals in the area; the different testing of collection methodologies (interviews, direct and dynamic observations); the application of the indicators in the field, in order to verify their viability and practicality in the context; the systematization of the data obtained; and the improvement of the initial indicators. The collected data were analyzed through Discursive Textual Analysis (DTA) and supported conclusions on the feasibility and relevance of the proposed indicators. The results show that the collection methodologies may vary according to the context in which they will be applied, and in the present research and in the context of a pandemic, the collection became feasible through an online form and direct observations. The indicators are shown as an effective and practical evaluation tool for decision making and constant improvement of the analyzed technology. A final proposal of indicators was built so that in similar contexts they can be applied. In addition, the impact of technology on the educational process was analyzed through a cube analysis considering eight possible scenarios. Technology has a positive impact and can contribute to a better experience and connection with nature in non-formal education spaces.
Elaboration and analysis of environmental education indicators for the conservation of biodiversity mediated by technology in the Iguaçu National Park
Keywords: Educação ambiental não formal; Aplicativo móvel; Unidade de conservação; Turismo; Non-formal environmental education; Mobile application; Conservation unit; Tourism; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES